All Aspects of Contemplation in Islam: اسلام میں غورو فکر کے ہمہ جہت پہلو - Hamzah, Muhammad; Ali, Hafiz Syed Saqib; Sindhu, Dr. Jamil Ahmad (Al Khadim Research Journal of Islamic Culture and Civilization, 2023)
Ever since this universe came into existence and especially since life was born in the world man has been trying to know the secret and purpose of this universe and Life by using new ideas and innovative methods. All the time to know this universe and its insistence and codes. In this article we will see how the religion of Islam has encouraged man to know about this universe to understand it and to use all disabilities to reveal these hidden secrets. https://doi.org/10.5281/zenodo.10519396